Tick salivary compounds: their role in modulation of host defences and pathogen transmission - Kazimirova, Maria; Stibraniova, Iveta (Frontiers in Cellular and Infection Microbiology, 2013)
Ticks require blood meal to complete development and reproduction. Multifunctional tick salivary glands play a pivotal role in tick feeding and transmission of pathogens. Tick salivary molecules injected into the host modulate host defence responses to the benefit of the feeding ticks. To colonize tick organs, tick-borne microorganisms must overcome several barriers, i.e., tick gut membrane, tick immunity, and moulting. Tick-borne pathogens co-evolved with their vectors and hosts and developed molecular adaptations to avoid adverse effects of tick and host defences. Large gaps exist in the knowledge of survival strategies of tick-borne microorganisms and on the molecular mechanisms of tick-host-pathogen interactions. Prior to transmission to a host, the microorganisms penetrate and multiply in tick salivary glands. As soon as the tick is attached to a host, gene expression and production of salivary molecules is upregulated, primarily to facilitate feeding and avoid tick rejection by the host. Pathogens exploit tick salivary molecules for their survival and multiplication in the vector and transmission to and establishment in the hosts. Promotion of pathogen transmission by bioactive molecules in tick saliva was described as saliva-assisted transmission (SAT). SAT candidates comprise compounds with anti-haemostatic, anti-inflammatory and immunomodulatory functions, but the molecular mechanisms by which they mediate pathogen transmission are largely unknown. To date only a few tick salivary molecules associated with specific pathogen transmission have been identified and their functions partially elucidated. Advanced molecular techniques are applied in studying tick-host-pathogen interactions and provide information on expression of vector and pathogen genes during pathogen acquisition, establishment and transmission. Understanding the molecular events on the tick-host-pathogen interface may lead to development of new strategies to control tick-borne diseases.